2021
DOI: 10.3390/nu13113780
|View full text |Cite
|
Sign up to set email alerts
|

Time-Restricted Feeding Restores Obesity-Induced Alteration in Adipose Tissue Immune Cell Phenotype

Abstract: Studies suggest that time-restricted feeding (TRF) may prevent obesity and its commodities. At present, little is known about how TRF impacts immune cells, and whether such an effect is linked to altered metabolic parameters under condition of a high-fat diet (HFD)-induced obesity. To address these issues, we conducted a study in which we determined whether TRF has therapeutic efficacy against weight gain, adiposity, as well as associated immune cell disturbance found in obese mice. Six-week-old male C57BL/6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…In addition, TRF reduced mRNA expression of the transcription factor Cepba in BM cells. In summary, TRF is an effective dietary strategy to reduce overproduction of monocytes during obesity, which may be associated with the reduced CD11c + adipose tissue macrophages and insulin resistance seen in our previous study (22). LT-HSC, long-term hematopoietic stem cells; MPP, multipotent progenitors; Pre-GM, pre-granulocyte macrophage progenitors; GMP, granulocyte macrophage progenitors; LSK, Lin -Sca-1 + c-Kit + ; LK, Linc-Kit + cells; Lepr, leptin receptor; ↑H, increased by HFD ad libitum; ⨂, inhibited by TRF intervention.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…In addition, TRF reduced mRNA expression of the transcription factor Cepba in BM cells. In summary, TRF is an effective dietary strategy to reduce overproduction of monocytes during obesity, which may be associated with the reduced CD11c + adipose tissue macrophages and insulin resistance seen in our previous study (22). LT-HSC, long-term hematopoietic stem cells; MPP, multipotent progenitors; Pre-GM, pre-granulocyte macrophage progenitors; GMP, granulocyte macrophage progenitors; LSK, Lin -Sca-1 + c-Kit + ; LK, Linc-Kit + cells; Lepr, leptin receptor; ↑H, increased by HFD ad libitum; ⨂, inhibited by TRF intervention.…”
Section: Discussionmentioning
confidence: 61%
“…Since ATM are associated with obesity-associated insulin resistance ( 11 , 54 56 ), reduced numbers of monocytes by TRF may result in fewer ATM and perhaps also with less proinflammatory profile for these ATM. Indeed, we previously reported that TRF intervention reduced numbers of total and proinflammatory ATM, along with the improvement of insulin resistance in overweight and obese mice ( 22 ). Real-time PCR of the total adipose tissue for the macrophage-associated genes Adgre1 (F4/80) and Itgax (CD11c) also indicated that TRF decreased proinflammatory ATM infiltration ( Figure 1M ), consistent with our previous findings ( 22 ) ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Additionally, they reported that fasting for as little as 4 h in mice significantly decreased macrophages in various tissues, however the kidneys were not examined. Lastly, Lee et al performed a study in which mice were fed a high fat diet for 8 weeks and some mice underwent a 14-h TRF [ 31 ]. They reported that TRF significantly decreased adipose tissue macrophages, which were CD45+CD11b+F4/80+, as well as CD11c+ macrophages, similar to our current findings of these same cells being decreased significantly in the kidneys of hypertensive mice that underwent a 12-h TRF for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%